2013
DOI: 10.3310/hta17190
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility and cost-effectiveness of selective nerve root blocks in patients considered for lumbar decompression surgery: a systematic review and economic model

Abstract: Reports are published in Health Technology Assessment (HTA) if (1) they have resulted from work for the HTA programme, and (2) they are of a sufficiently high scientific quality as assessed by the reviewers and editors.Reviews in Health Technology Assessment are termed 'systematic' when the account of the search appraisal and synthesis methods (to minimise biases and random errors) would, in theory, permit the replication of the review by others. HTA programmeThe HTA programme, part of the National Institute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 74 publications
(173 reference statements)
2
20
0
Order By: Relevance
“…68 One recent review concluded that adding SNRB to diagnostic work-ups in patients with lumbar radiculopathy being considered for surgery was not cost-effective. 112 Surgery Few randomized studies have evaluated surgical treatment for neck pain, and none have done so for mechanical pain. In a randomized study comparing anterior decompression and fusion operations, physical therapy, and hard collar immobilization in 81 patients with cervical radiculopathy, Persson et al 113,114 found greater reductions in pain (29% for surgery, 19% for physical therapy, and 4% for cervical collar) and improvements in muscle strength and sensory loss in the surgical group than in the other treatment groups.…”
Section: Injectionsmentioning
confidence: 99%
“…68 One recent review concluded that adding SNRB to diagnostic work-ups in patients with lumbar radiculopathy being considered for surgery was not cost-effective. 112 Surgery Few randomized studies have evaluated surgical treatment for neck pain, and none have done so for mechanical pain. In a randomized study comparing anterior decompression and fusion operations, physical therapy, and hard collar immobilization in 81 patients with cervical radiculopathy, Persson et al 113,114 found greater reductions in pain (29% for surgery, 19% for physical therapy, and 4% for cervical collar) and improvements in muscle strength and sensory loss in the surgical group than in the other treatment groups.…”
Section: Injectionsmentioning
confidence: 99%
“…Selective nerve root blocks with only local anesthetic have been done historically as a mode of diagnosis and as a predictive guideline for patients considering lumbar decompression surgery despite its accuracy having been questioned 40,41. Adding steroid to local anesthetic can improve the duration of pain relief of injections, thus many injections can be both diagnostic and therapeutic.…”
Section: Diagnosismentioning
confidence: 99%
“…Additionally, probabilistic sensitivity analysis, a standard method of integrating uncertainty about many variables simultaneously, was performed. 26 …”
Section: Discussionmentioning
confidence: 99%